Delta-9-tetrahydrocannabinol ameliorates D-galactose/ aluminium chloride-induced Alzheimer’s-like cognitive deficit in rats via neurogenesis in their Hippocampus - Zakaria, Fatin Nadzirah; Mohd Moklas, Mohamad Aris; Baharuldin, Mohamad Taufik Hidayat; Mat Taib, Che Norma; Ab Hamid, Hasiah; Abdul Hamid, Hafizah; Musa Chiroma, Samaila (Elsivier, 2024)
Chronic administration of D-galactose and aluminium chloride (D-gal/AlCl3) has been associated with neurodegenerative diseases, such as Alzheimer’s disease (AD). Delta- 9-tetrahydrocannabinol (Δ9THC) is the key psychoactive constituent in Cannabis sativa and has shown promising memory-enhancing capability. This study evaluated the therapeutic effects of Δ9THC.